Cevap :
[tex] {(x - 6)}^{2} = {(2 \sqrt{13} + 6) - 6)} ^ {2} = 4 \times 13 = 52[/tex]
Adım adım açıklama:
kusura bakma buraya atmak zorunda kaldım diğer soruma cevap hakkı dolmuştu
![Görseli göster Aysegokcay1111](https://tr-static.eodev.com/files/d0b/9060e54c9e445b509af0e3b4e77d739f.jpg)
![Görseli göster Aysegokcay1111](https://tr-static.eodev.com/files/d86/17b827dffaa746c0e45704433aac196e.jpg)
[tex] {(x - 6)}^{2} = {(2 \sqrt{13} + 6) - 6)} ^ {2} = 4 \times 13 = 52[/tex]
Adım adım açıklama:
kusura bakma buraya atmak zorunda kaldım diğer soruma cevap hakkı dolmuştu